Homo Ludens and No End: A Bibliography of International Reflections on Johan Huizinga’s Masterwork - Hanssen, Léon (Into the Magic Circle: Rethinking Homo Ludens, 2024)
Johan Huizinga’s theory of play as set out in his Homo Ludens encouraged many other scholars all over the world to reflect upon play and games in culture. The wish to get an overview of this productive reception was one of the main drives behind the compiling of this ‘open’ bibliography (open, because reflection on Huizinga is ongoing and updates will be welcomed in next editions).